A novel fibronectin type III module binding motif identified on C-terminus of Leptospira immunoglobulin-like protein, LigB - Lin, Yi-Pin (2009)
Infection by pathogenic strains of Leptospira hinges on the pathogen’s ability to adhere to host cells via extracellular matrix such as fibronectin (Fn). Previously, the immunoglobulin-like domains of Leptospira Lig proteins were recognized as adhesins binding to N-terminal domain (NTD) and gelatin binding domain (GBD) of Fn. In this study, we identified another Fn-binding motif on the C-terminus of the Leptospira adhesin LigB (LigBCtv), residues 1708–1712 containing sequence LIPAD with a β-strand and nascent helical structure. This motif binds to 15th type III modules (15F(3)) (K(D) = 10.70 μM), and association (k(on) = 600 M(−1) s(−1)) and dissociation (k(off) = 0.0129 s(−1)) rate constants represents a slow binding kinetics in this interaction. Moreover, pretreatment of MDCK cells with LigB(1706–1716) blocked the binding of Leptospira by 39%, demonstrating a significant role of LigB(1706–1716) in cellular adhesion. These data indicate that the LIPAD residues (LigB(1708–1712)) of the Leptospira interrogans LigB protein bind 15F(3) of Fn at a novel binding site, and this interaction contributes to adhesion to host cells.